A successful cesarean section in a pregnant woman with A (H1N1) influenza requiring ECMO support - Łysenko, Lidia; Zaleska-Dorobisz, Urszula; Blok, Radosław; Dumański, Andrzej; Zielińska, Marzena; Kustrzycki, Wojciech; Durek, Grażyna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
A 24-year-old pregnant woman (29.4 weeks of gestation) with A (H1N1) influenza-associated adult respiratory distress syndrome was admitted to the intensive care unit. The patient was connected to femoral-jugular veno-venous extracorporeal membrane oxygenation (ECMO) 8 hours after admission. On the 7th day of ECMO support, due to the increasing threat to the life of the mother and the fetus, a decision was made to carry out a cesarean section (CS) without discontinuing the ECMO support. The CS was performed uneventfully under general anesthesia, 5 hours after the discontinuation of heparin infusion. A live, premature 1200 g female neonate was delivered. No complications occurred in the perioperative period. On the 17th day, the patient was successfully weaned off the ECMO and discharged 10 days later. The newborn was discharged from the hospital in good health 41 days after the delivery.